A closed-body preclinical model to investigate blast-induced spinal cord injury - Norris, Carly; Weatherbee, Justin; Murphy, Susan; Marquetti, Izabele; Maniakhina, Lana; Boruch, Alan; VandeVord, Pamela (Frontiers in Molecular Neuroscience, 2023)
Blast-induced spinal cord injuries (bSCI) are common and account for 75% of all combat-related spinal trauma. It remains unclear how the rapid change in pressure contributes to pathological outcomes resulting from these complex injuries. Further research is necessary to aid in specialized treatments for those affected. The purpose of this study was to develop a preclinical injury model to investigate the behavior and pathophysiology of blast exposure to the spine, which will bring further insight into outcomes and treatment decisions for complex spinal cord injuries (SCI). An Advanced Blast Simulator was used to study how blast exposure affects the spinal cord in a non-invasive manner. A custom fixture was designed to support the animal in a position that protects the vital organs while exposing the thoracolumbar region of the spine to the blast wave. The Tarlov Scale and Open Field Test (OFT) were used to detect changes in locomotion or anxiety, respectively, 72 h following bSCI. Spinal cords were then harvested and histological staining was performed to investigate markers of traumatic axonal injury (β-APP, NF-L) and neuroinflammation (GFAP, Iba1, S100β). Analysis of the blast dynamics demonstrated that this closed-body model for bSCI was found to be highly repeatable, administering consistent pressure pulses following a Friedlander waveform. There were no significant changes in acute behavior; however, expression of β-APP, Iba1, and GFAP significantly increased in the spinal cord following blast exposure (p < 0.05). Additional measures of cell count and area of positive signal provided evidence of increased inflammation and gliosis in the spinal cord at 72 h after blast injury. These findings indicated that pathophysiological responses from the blast alone are detectable, likely contributing to the combined effects. This novel injury model also demonstrated applications as a closed-body SCI model for neuroinflammation enhancing relevance of the preclinical model. Further investigation is necessary to assess the longitudinal pathological outcomes, combined effects from complex injuries, and minimally invasive treatment approaches.